DIFFRACTION IMAGING OF SEISMIC WAVES FOR DISCONTINUITY BIDANG DETECTION USING PLANE WAVE DECOMPOSITION - WIDYATMOKO (NIM : 22310320); Pembimbing : Prof Dr.rer.nat Awali Priyono, AMRI
Diffraction occurs when seismic wavefronts hits the subsurface discontinuous smaller than the seismic wavelength. Examples of the discontinuous bidangs, such as faults, pinch outs, salt bondary, fracture and form a small object / local heterogeneous. Although the interpretation of discontinuous objects can actually be done with the usual standard seismic processing, but the method has limited resolution. At the time of seismic waves emitted hit discontinuous areas below the surface, there will be the effects of diffraction. In this case the seismic wave diffraction can be identified as having information hidden from discontinued geometry. Separation of signal reflection and diffraction patterns should be done with a good method to avoid the hidden of diffraction by signal reflections that cause weakening of the characters so that the potential of the information does not appear. Plane Wave Decomposition Method filter (PWD) will be used in this study to separate the reflection and diffraction by a distinct form of signal bidangs in the τ-p domain (tau-pi), which is the linear character of the curve for the reflection and diffraction. Simple experiments performed on discontinued models that can adequately describe the representation of complex geological conditions indicate that PWD filter method can separate signal reflection and diffraction patterns.